2003
DOI: 10.1603/0022-2585-40.4.534
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofBorrelia burgdorferi,Ehrlichia chaffeensis, andAnaplasma phagocytophilumin Ticks (Acari: Ixodidae) from a Coastal Region of California

Abstract: A study was conducted in Santa Cruz County to estimate the prevalence and distribution of the agents of Lyme disease, human granulocytic (HGE), and human monocytic (HME) ehrlichiosis in 1,187 adult ixodid ticks collected from eight public-use recreation areas over a 2-yr period. Borrelia burgdorferi, the causative agent of Lyme disease, was detected by a polymerase chain reaction (PCR) in 44 of 776 (5.67%) Ixodes pacificus ticks and in 3 of 58 (5.17%) Dermacentor variabilis ticks. Anaplasma phagocytophilum, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 22 publications
(15 reference statements)
0
59
0
3
Order By: Relevance
“…The low disease incidence is consistent with patterns of human disease reported in the far western states (Bacon et al 2008). As has been reported in other parts of its range Holden et al 2003;Lane et al 2004), the infection rates of B. burgdorferi in host-seeking I. pacificus in British Columbia are very low (Ogden et al 2008c), likely because immature ticks preferentially feed on lizards, which are incompetent hosts (Lane and Quistad 1998;Casher et al 2002). Thus in British Columbia, the risk of human infection with B. burgdorferi is very low, partly because of the widespread but focal nature of the established tick populations and the low prevalence of B. burgdorferi in vector ticks (Ogden et al 2008c).…”
Section: Natural Historymentioning
confidence: 88%
“…The low disease incidence is consistent with patterns of human disease reported in the far western states (Bacon et al 2008). As has been reported in other parts of its range Holden et al 2003;Lane et al 2004), the infection rates of B. burgdorferi in host-seeking I. pacificus in British Columbia are very low (Ogden et al 2008c), likely because immature ticks preferentially feed on lizards, which are incompetent hosts (Lane and Quistad 1998;Casher et al 2002). Thus in British Columbia, the risk of human infection with B. burgdorferi is very low, partly because of the widespread but focal nature of the established tick populations and the low prevalence of B. burgdorferi in vector ticks (Ogden et al 2008c).…”
Section: Natural Historymentioning
confidence: 88%
“…Attempts to detect A. phagocytophilum in other species of ixodid ticks in California have been unsuccessful (2,19 (18). The difference in seasonality between the two areas may be due to the differences in vectors and weather.…”
Section: Discussionmentioning
confidence: 99%
“…However, a wide range of coinfection scenarios exist in nature, and the frequency of their occurrences is unknown. Although ticks may harbor both pathogens, prevalence studies in endemic areas throughout the United States have shown that coinfection rates may be as little as 1 to 6% (6,17) or as high as 26% (3), whereas the rate of ticks singly infected with B. burgdorferi can be up to 40% (6) and the rate of ticks singly infected with A. phagocytophilum can be up to 20% (19). In addition, transmission time, from tick to host, may differ for each pathogen (20).…”
Section: Discussionmentioning
confidence: 99%